2013
DOI: 10.1177/0363546513490648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air-Pulsed Cryotherapy on Neuromuscular Recovery Subsequent to Exercise-Induced Muscle Damage

Abstract: Four applications of air-pulsed cryotherapy in the 3 days after a strenuous eccentric exercise are ineffective overall in promoting long-term muscle recovery. Further studies taking into account the amount of exercise-induced muscle damage would allow investigators to make stronger conclusions regarding the inefficiency of this recovery modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 37 publications
5
60
5
Order By: Relevance
“…This may be an indicator of provoked muscle damage, which can be seen in Figures 2 and 3. DOMS peaked after 48 hours in both groups which is consistent with the results of previous research 5,7. The objective measures, namely, VJP and the corresponding PPO, showed the greatest decline after 48 hours of recovery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be an indicator of provoked muscle damage, which can be seen in Figures 2 and 3. DOMS peaked after 48 hours in both groups which is consistent with the results of previous research 5,7. The objective measures, namely, VJP and the corresponding PPO, showed the greatest decline after 48 hours of recovery.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of cryotherapy are believed to be a result of peripheral vasoconstriction, which leads to the reduction of the inflammatory process due to decreased cell metabolism 3,4. Commonly used cryotherapy procedures consist of external applications, such as cold packs,5 ice cuffs,6 cold air,7 ice sprays,8 cold-water immersion (CWI),9 whole-body cryotherapy chambers,10 whole-body cryochambers using liquid nitrogen,11 cooling vests,12 or any other combination of these methods, as well as cold-water ingestion 13,14. The latter procedure has resulted in conflicting results 15,16…”
Section: Introductionmentioning
confidence: 99%
“…We have been unable to investigate the recovery of the measured variables over a longer time period after the NMES because of logistical constraints. However the variables measured in the present study have been shown to completely recover within weeks after a voluntary EIMD [13], [25][28].…”
Section: Methodscontrasting
confidence: 50%
“…This decrease promotes physiological responses such as decreased cell metabolism, posttraumatic capillary dysfunction, and enzymatic activity 4,23. Collectively, these responses may preserve muscle-fiber function and reduce exercise-induced muscle-damage symptoms 23. On the other hand, cold application may transitorily impair muscular performance.…”
Section: Discussionmentioning
confidence: 99%